Haemorrhagic cerebral air embolism from an atrio-oesophageal fistula following atrial fibrillation ablation. - Koa-Wing,M; Jamil-Copley,S; Ariff,B; Kojodjojo,P; Lim,PB; Whinnett,Z; Rajakulendran,S; Malhotra,P; Lefroy,D; Peters,NS; Davies,DW; Kanagaratnam,P (Perfusion, 2014)
We report the case of a man found unconscious three weeks following atrial fibrillation (AF) ablation. Cranial and thoracic imaging demonstrated multiple areas of pneumo-embolic infarction secondary to an atrio-oesophageal fistula (AEF). AEF is a recognised, but rare, complication of AF ablation.(1-8) Early recognition is critical as the mortality is 100% without surgical intervention. We consider the postulated mechanisms of AEF formation, the spectrum of clinical presentation, investigations and treatment.